Utilization of Satellite Gravimetric Data to Estimate the Location of the Magma Chamber of Slamet Volcano, Central Java, Indonesia - Sehah Sehah; Sorja Koesuma; Urip Nur Wijayanto Prabowo; Aina Zahra Ikhwana (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Satellite gravimetric data can be utilized to map the gravity anomaly on the earth's surface, especially for difficult, extreme, and large areas. In this study, satellite gravimetric data has been used to estimate the location of the magma chamber of Slamet volcano, Indonesia. Information on the magma chamber is very useful for knowing the volcanic characteristics and activity, thus helping pre-mitigation efforts to catastrophic eruptions that occur. The stages in the study which have been carried out include data access, correction, reduction, modeling, and interpretation. The satellite gravimetric data that has been accessed is GGMplus data. After several corrections and reductions are done, the complete Bouguer anomalies (CBA) data are obtained with values ranging from 11.889 – 117.429 mGal. Filtering process using the upward continuation has been applied to obtain regional anomalies data. The regional anomalies data are corrected to the CBA data, so that the residual gravity anomalies data are obtained. The lowest gravity anomaly value is located at positions of 109.21967 E and 7.24281 S which is interpreted to be the location of the magma chamber of Slamet Volcano that is currently still active. The result of modeling of the residual gravity anomalies data indicate that the position of the magma chamber of Slamet Volcano is estimated to be relatively under the cone with a density lower than the surrounding rock densities, i.e. 1.50 – 1.75 g/cm3. The study results have a good match with the geological map of the study area.